Optimizing Warehouse Distribution Routes During Eid Season Using Saving Matrix and Nearest Insert Method - Gita Kurnia; Ni Putu Dewi Velicia Darmawan (Jurnal Logistik Indonesia, 2021)
Arranging an optimal distribution system is a challenging step in every company who runs logistics activities because it is one of the crucial factors to achieve high customers’ satisfaction level. This problem becomes more complex during the high or special seasons such as Christmas, new year, etc. In Indonesia, high season for logistics usually during the Eid season. During that special season, the demand increases while the resource decreases due to long national holiday. Failed to find an optimal distribution system might lead to a huge loss for the company. Therefore, to overcome this problem, logistics company should optimize the distribution system including optimizing the route and vehicles utilization. This paper aims to help a logistics company based in Bali, Indonesia, to find an optimal distribution route during the Eid Season. This company find difficulty to fulfil the customer demands especially during the Eid Season. To find an optimal route for the company, this paper applies Saving Matrix and Nearest Insert methods. These two algorithms are chosen because both of them have a simple procedure. Thus, it can save the computational time. Besides, a simple procedure will help the company to reuse the proposed methods for the next application. Data collection and observation in this paper were carried out during one week of Eid season in 2019. The computational results show that the optimal route is able to deliver all items before the due date with total distribution time 7 hours 16 minutes. Compare with the existing route, the proposed route reduces the total cost by 30%.